Introducing open montage: Material performativity in urban media configurations in space - Mel Jordan; Giorgia Rizzioli (NECSUS, 2024)
This article introduces the concept of ‘open montage’, a framework developed to explore the media configurations between art, cinema, and urban space and the entangled relations this interplay presents in terms of publics and publicness. The unique perspective of our open montage concept enables us to put forth a framework for artistic arrangements in space, which liberates them from the confines of representation and human interpretation. Our argument for the notion of open montage also lies in its ability to challenge conventional theories about spectators, presenting them as active participants in a process of material embodiment bound by spatial and temporal constraints. The structure of our article revolves around the theme of openness. We draw on art, critical theory, and media studies literature to demonstrate the concept of open montage and its application in spatial coordinates. Subsequently, we explore the lens of posthumanism, aiming to challenge the linguistic account characterising the public dimension evident in the montage of our media configurations in space.